A real-world comparison of clinical effectiveness in patients with rheumatoid arthritis treated with upadacitinib, tumor necrosis factor inhibitors, and other advanced therapies after switching from an initial tumor necrosis factor inhibitor - Caporali, R; Kadakia, A; Howell, O; Patel, J; Milligan, J; Strengholt, S; Barlow, S; Taylor, PC (Springer, 2024)
INTRODUCTION: This study compared the clinical effectiveness of switching from tumor necrosis factor inhibitor (TNFi) to upadacitinib (TNFi-UPA), another TNFi (TNFi-TNFi), or an advanced therapy with another mechanism of action (TNFi-other MOA) in patients with rheumatoid arthritis (RA). METHODS: Data were drawn from the Adelphi RA Disease Specific Programme™, a cross-sectional survey administered to rheumatologists and their consulting patients in Germany, France, Italy, Spain, the United Kingdom, Japan, Canada, and the United States from May 2021─January 2022. Patients who switched treatment from an initial TNFi were stratified by subsequent therapy of interest: TNFi-UPA, TNFi-TNFi, or TNFi-other MOA. Physician-reported clinical outcomes included disease activity (with formal DAS28 scoring available for 29% of patients) categorized as remission, LDA, MDA and HDA and pain were recorded at initiation of current treatment and ≥ 6 months from treatment switch. Fatigue and treatment adherence were measured ≥ 6 months from treatment switch. Inverse-probability–weighted regression adjustment compared outcomes by subsequent class of therapy: TNFi-UPA versus TNFi-TNFi, or TNFi-UPA versus TNFi-other MOA. RESULTS: Of 503 patients who switched from their first TNFi, 261 were in TNFi-UPA, 128 in TNFi-TNFi, and 114 in TNFi-other MOA groups. At the time of switch, most patients had moderate/high disease activity (TNFi-UPA: 73%; TNFi-TNFi: 52%; TNFi-other MOA: 60%). After adjusting for differences in characteristics at point of switch, patients in TNFi-UPA group (n=261) were significantly more likely to achieve physician-reported remission (67.7% vs. 40.3%; p=0.0015), no pain (55.7% vs. 25.4%; p=0.0007), and complete adherence (60.0% vs. 34.2%; p=0.0049) compared with patients in TNFi-TNFi group (n=121). Similar findings were observed for TNFi-UPA versus TNFi-other MOA groups (n=111). CONCLUSION: Patients who switched from TNFi to UPA had significantly better clinical outcomes of remission, no pain, and complete adherence than those who cycled TNFi or switched to another MOA.